Impact of germination versus non-germination on nutritional and functional potentials of two rice varieties (Ranjit and Ahu Kalogoria) available in three different districts of Assam, India - Khatun, Laky; Ray, Subhajit; Baruah, Dulal Chandra (Journal of Food Technology Research, 2023)
The main purpose of this study is to explore the effect of germination and non-germination on the nutritional and functional properties of rice varieties. In this study, two types of rice—Ahu Kalogoria (germinated) and Ranjit (non-germinated)—and the husk of Ahu variety rice were chosen and described based on their accession numbers. The rice came from Goalpara, Chirang, and Kokrajhar in the Indian state of Assam. Finally, their calorific values and nutritional and functional constituents were examined. Standard and validated experimental protocols are considered for the assessment of all parameters during this study. RC-0648663 (Ranjit rice, Chirang) and LK1-0646984 (Ahu Kalogoria, Goalpara) contain higher calorific values, i.e., 361.24±1.95aKcal/100gm and 356.35±1.32aKcal/100gm, and the Husk LK1-0646984H (Ahu Kalogoria husk, Goalpara) contains 222.51±3.07cKcal/100gm. Mg was found as a potential mineral in all varieties. Optimum total flavonoid content (TFC) and total phenolic content (TPC) were found in LK1-0646984(324.75±0.58amg QE/100gm; 353.7±1.66a mgGAE/100gm), LK1-0646984H (345.82±1.57bmgQE/100gm; 440.12±0.88b mg GAE/100gm) and RC-0648663 (69.375±1.3cmg QE (Quercetin equivalent) /100 gm; 106.79±0.54c mgGAE/100gm) respectively. The DPPH (2, 2-diphenyl 1-picrylhydrazyl) radical scavenging activity of LK1-0646984, LK1-0646984H, and RC-0648663 was determined to be maximum at 63.25±0.43a%, 69.36±0.31b%, and 34.2±0.2c%. Experimental results revealed that vitamin B5 content was higher in LK1-0646984 of 6.52mg/kg in comparison to RC-0648663 (Ranjit rice, Chirang) of 0.96mg/kg. Vitamin B1 was found at its maximum (3.53mg/kg) in LK1-0646984H. Therefore, the germinated rice variety (LK1-0646984) was found to be superior in quality to the non-germinated variety based upon nutritional, functional, and energy assessments, provide significant health benefits, and gain importance in the present socioeconomic scenario.